Acesso às práticas integrativas e complementares em saúde no sus: uma análise sob a ótica dos usuários - Magalhaes, Fabiola Fernandes Bersot (2019)
It is increasingly evident the use of alternative and complementary medicine for health treatment in the world. Integrative and Complementary Practices in Health (PICS), as they are known in Brazil, seek to stimulate natural mechanisms for health promotion, disease prevention and health recovery, with an emphasis on welcoming listening, developing the therapeutic link and integrating the being with the environment and society. The implementation of the National Policy on Integrative and Complementary Practices (PNPIC) in the country since 2006 is considered an advance and an important landmark in the introduction of unconventional practices in the Unified Health System (SUS). However, the existing problems that hinder the development of this policy mean that implementation remains at the periphery of SUS, with little prospect of entering the center of the system. The present study aims to analyze the access to these practices, based on listening to users of the public health system of the city of Vitória-ES. Understanding that access is an imprecise, complex term, with little clarity in its relation to the use of health services, the research will discuss this perspective based on Frenk's theoretical framework, which proposes, in an extended analysis, to systematize the flow of events between the moment when the health need is perceived until the effectiveness of the care, besides the determination of the demand and entrance in the health services and the continuity of this care. It is a qualitative study of exploratory character that is defined in the encounter with the users involved in a municipal APS. Sampling occurred randomly, totaling 29 USF users. Data were collected through semi-structured interviews and participant observation. After the saturation of the data, the analysis was carried out in the perspective of access to Integrative and Complementary Practices in Health and how a certain phenomenon manifests itself in the desires, activities, procedures and daily interactions. It was verified, when reaching the singularities of the therapeutics observed, that even with the proposal of an extended access model, it is not possible to contemplate all the peculiarities of the access to the PICS. It was possible to understand that this access depends on the organization of the service and the type of offer available, related to the degree of institutionalization of the PICS in the public health network, and that the user's access to the service will depend, in addition to the social characteristics, of individual characteristics and subjective aspects.